Rancangan Strategi Menangani Ancaman Perang Hybrida Melalui Patroli Maritim di Kawasan Laut China Selatan - Syafruddin, Hadi; Judijanto, Judijanto (Rekayasa, 2022)
The ever-changing dynamics in the South China Sea are making international relations even hotter, especially Western countries that feel threatened by China's claims to the South China Sea region with its Nine Dash Line. The South China Sea claimed by China is the North Natuna Sea which is included in the territory of the Republic of Indonesia. Lately the disputed countries use a new strategy of hybrid war that has been waged by the Chinese state in making a coercion by demonstrating capability in terms of strength. This problem makes Indonesia whose territory is affected in the North Natuna Sea must quickly anticipate in response to hybrid warfare by firmly declaring itself as a non-claimant states participating in the arena of dispute in an effort to claimant-states (state parties) in seizing rights in the South China Sea creating an unconventional war called hybrid warfare. One strategy using the SWOT method can conclude that in a prominent variable with opportunities where variables of cooperation with foreign countries greatly help realize the game, security and stability of the region in the Natuna Sea. The strategy used by increasing the variable strength (Strong) and opportunity (Opportunity) so as to increase the security and stability of the NKRI region in the Natuna Sea.